Transesterification of palm oil to produce biodiesel - 290025 Azura Razali; Mohd. Nazlan Mohd. Muhid, supervisor; Fakulti Sains (2006)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2006